A Comparative Study Between Conventional Reading Strategies And KWL Technique On Students’ Reading Comprehension At Grade 8 Of SMP Negeri 9 Kendari - Ramadhan, Mukti; Yazid, Muhammad; Tambunan, Tambunan (Journal of Language Education and Educational Technology (JLEET), 2017)
Understanding reading passage requires the activation of background knowledge, vocabulary competence and the understanding of the rules of the target language to construct the meaning of the text. This research is set out to discover the effective teaching to improve the reading comprehension by activating the students’ background knowledge, connecting it to the current text to read and producing the meaning. Appointing to the connection between the background knowledge to the text, this research investigates the comparison between the traditional group work of reading and use of KWL technique for teaching reading at grade 8 of SMPN 9 Kendari. The objective of this study is to investigate, there is or not a significant difference of reading comprehension between students who learn reading based on conventional teaching and those who learn based on KWL technique. This study applied matching pre-post comparison group design, which involves two cohorts namely control and experimental group. The hypothesis of this study is “there is a significant difference of reading comprehension between the students who learn reading based on traditional group work of reading and those who learn reading based on task based learning. Using independent t-test to evaluate the hypothesis of this study (sig. 2-tailed = 0.00 < 0.05), reveals that there is a significant difference of reading comprehension between students who learn reading based on traditional group work of reading and those learn based on task based learning. This study is also covers the students’ motivation in learning reading based on traditional group working and task based learning. It shows that students who learn reading English text by using KWL technique were positively motivated than those who do not. Therefore, this study suggests to use KWL technique in the teaching of reading especially at Grade 8th of SMPN 9 Kendari. It also suggested that further research to apply KWL technique to improve the students’ reading comprehension can be applied in the form paperless or digital form of KWL to make it more attractive and dynamically accessible without considering the geographical span.